PDE4B-associated regulation of placental HSD11B2 in fetal growth restriction in a prenatal caffeine exposure model - Xinrui Cao; Ping Jiang; Luting Yu; Man Fang; Xiuping Jin; Hui Wang (Chemico-Biological Interactions, 2026)

Point-of-use water treatment: energy-autonomous synergistic solar photothermal-piezocatalysis on MXene/Bi2WO6 membranes for distributed removal of sulfonamide antibiotics - Junzhuo Cai; Jiaxin Liu; Yu Bon Man; Jixiang Chen; Luting Li; Xiaoxun Xu; Chengyi Huang; Changlian Xu; Guochun Lv; Xin Qi; Zhanbiao Yang; Guiying Wang; et al. (Water Research, 2025)

Mechanism and marker of voriconazole–induced liver injury: insights from a quantitative systems toxicology approach - Qian Du; Yulan Qiu; Luting Yang; Chuhui Wang; Mengmeng Teng; Jiaojiao Chen; Yu Luo; Jinyao Sun; Taotao Wang; Siying Chen; Yalin Dong (Regulatory Toxicology and Pharmacology, 2025)

Inhibition of placental 11β-HSD2 expression through cAMP/PKA signaling pathway induces intrauterine growth retardation - Caiyun Ge; Luting Yu; Man Fang; Xinrui Cao; Huijun Chen; Hui Wang (Toxicology Letters, 2025)

Engineering exciton dissociation and intermolecular charge transfer to boost superoxide radical in conjugated microporous polymers for simultaneous elimination of coexisting contaminants - Weijie Zhang; Xinye Luo; Luting Liu; Meilin Lei; Quan Wan; Bing Yi; Fengtao Yu; Hai Yang (Chemical Engineering Journal, 2024)

An efficient loop closure detection method for communication-constrained bathymetric cooperative SLAM - Chi Qi; Teng Ma; Ye Li; Luting Lv; Yu Ling (Ocean Engineering, 2024)

Atorvastatin Promotes Pro/anti-inflammatory Phenotypic Transformation of Microglia via Wnt/β-catenin Pathway in Hypoxic-Ischemic Neonatal Rats - Luting Yu; Lingyi Huang; Yuanyuan Zhao; Shixi Liu; Ruixi Zhou; Yan Yue; Hao Sun; Xiaojuan Su; Qian Liu; Shiping Li; Junjie Ying; Fengyan Zhao; et al. (Molecular Neurobiology, 2024)
Inflammatory reaction plays a key role in the pathogenesis of hypoxic-ischemic encephalopathy (HIE) in neonates. Microglia are resident innate immune cells in the central nervous system and are profoundly involved in neuroinflammation. Studies have revealed that atorvastatin exerts a neuroprotective effect by regulating neuroinflammation in adult animal models of brain stroke and traumatic brain injury, but its role regarding damage to the developing brain remains unclear. This study aimed to clarify the effect and mechanism of atorvastatin on the regulation of microglia function in neonatal hypoxic-ischemic brain damage (HIBD). The oxygen glucose deprivation (OGD) of microglia and neonatal rat HIBD model was established. Atorvastatin, recombinant sclerostin protein (SOST), and XAV939 (degradation of β-catenin) were administered to OGD microglia and HIBD rats. The pathological changes of brain tissue, cerebral infarction volume, learning and memory ability of rats, pro-inflammatory (CD16 + /Iba1 + ) and anti-inflammatory (CD206 + /Iba1 + ) microglia markers, inflammation-related indicators (Inos, Tnfα, Il6, Arg1, Tgfb, and Mrc1), and Wnt/β-catenin signaling molecules were examined. Atorvastatin reduced OGD-induced pro-inflammatory microglia and pro-inflammatory factors, while increasing anti-inflammatory microglia and anti-inflammatory factors. In vivo, atorvastatin attenuated hypoxia-ischemia (HI)-induced neuroinflammation and brain damage. Mechanistically, atorvastatin decreased SOST expression and activated the Wnt/β-catenin signaling pathway, and the administration of recombinant SOST protein or XAV939 inhibited Wnt/β-catenin signaling and attenuated the anti-inflammatory effect of atorvastatin. Atorvastatin promotes the pro/anti-inflammatory phenotypic transformation of microglia via the Wnt/β-catenin pathway in HI neonatal rats. Atorvastatin may be developed as a potent agent for the treatment of HIE in neonates.

Bioactive chemical constituents from the marine-derived fungus Cladosporium sp. DLT-5 - Luting Dai; Qingyi Xie; Jiaocen Guo; Qingyun Ma; Li Yang; Jingzhe Yuan; Haofu Dai; Zhifang Yu; Youxing Zhao (Journal of Oceanology and Limnology, 2024)

Exposure to parabens and dysglycemia: Insights from a Chinese population - Yu Song; Mian Wang; Luting Nie; Wei Liao; Dandan Wei; Lulu Wang; Juan Wang; Qingqing Xu; Changsheng Huan; Zexin Jia; Zhenxing Mao; Chongjian Wang; et al. (Chemosphere, 2023)

Metabolic characteristics of voriconazole – Induced liver injury in rats - Qian Du; Mengmeng Teng; Luting Yang; Chao Meng; Yulan Qiu; Chuhui Wang; Jiaojiao Chen; Taotao Wang; Siying Chen; Yu Luo; Jinyao Sun; Yalin Dong (Chemico-Biological Interactions, 2023)